Preserved ictal responsiveness in right mesial temporal lobe epilepsy: metabolic correlates in posterior temporal networks with FDG-PET - Choo, Yi-Seul; Shon, Young-Min; Moon, Seung Hwan; Kim, Jeongsik; Park, Hea Ree; Joo, Eun Yeon; Seo, Dae Won (Frontiers in Neurology, 2025)
ObjectiveAutomatisms with preserved responsiveness (APR) represent a distinctive clinical feature in right mesial temporal lobe epilepsy (MTLE). This study aimed to investigate whether interictal FDG-PET hypometabolism correlates with impaired responsiveness during seizures.MethodsWe retrospectively analyzed 49 patients with right MTLE who underwent presurgical evaluation. Patients were stratified into APR+ (n = 16) and APR- (n = 33) groups based on a standardized four-domain assessment (orientation, memory, verbal command, motor execution). Interictal FDG-PET hypometabolism was visually scored on a three-point scale (0 = absent, 1 = moderate, 2 = severe) across 31 predefined brain regions by three blinded epileptologists. Group comparisons were performed using independent-sample t tests or Mann–Whitney U tests, with Bonferroni correction (p < 0.0016) and effect size estimation (Cohen’s d).ResultsAPR- patients exhibited significantly greater hypometabolism in the posterior lateral temporal cortex (p = 0.00061, Cohen’s d = 1.20) compared to APR+ patients. Although hypometabolic trends were also observed in posterior mesial (p = 0.00203) and posterior basal temporal regions (p = 0.00328), these did not survive multiple-comparison correction. No significant group differences were found in anterior temporal, frontal, insular, parietal, occipital, or subcortical regions. Contralateral hemispheric metabolism was preserved across all regions.ConclusionConsciousness impairment in right MTLE is specifically associated with posterior lateral temporal dysfunction, with broader posterior temporal vulnerability suggested by subthreshold trends. These findings identify posterior lateral temporal hypometabolism as a potential biomarker of impaired responsiveness in right MTLE and highlight the value of FDG-PET for characterizing consciousness-related network dysfunction.